Association of Low Serum Ferritin Levels with Melasma: A Case-Control Study at a Tertiary Care Hospital: Association of Low Serum Ferritin Levels with Melasma - Tahir, Raheel; Shahzad, Muhammad Khurram; Akhtar, Aliya; Badar, Sadaf; Farooq, Chamman (Pakistan Journal of Health Sciences, 2025)
Melasma is a common acquired hyperpigmentation disorder with multifactorial etiology, including hormonal influences, genetic predisposition, and environmental factors. Yet the relationship between serum ferritin levels and melasma remains unclear. Objective: To determine the association between low serum ferritin levels and melasma among patients presenting at a tertiary care hospital. Methods: This case-control study was conducted in the Department of Dermatology, Nishtar Hospital, Multan, from June 3, 2024, to December 2, 2024. A total of 114 participants were included, with 57 melasma cases and 57 age- and gender-matched controls. Serum ferritin levels were measured and compared between groups. Data were analyzed using SPSS version 23.0, with odds ratios (ORs) and p-values were calculated. Results: The mean age of participants was 24.67 ± 5.27 years and the mean BMI was 24.22 ± 2.17 kg/m². Low serum ferritin levels were significantly associated with melasma (p=0.002, OR=5.20). The association was stronger in males (p=0.002, OR=24.00), but not statistically significant in females (p=0.142, OR=2.81). Among participants with Fitzpatrick Skin Type III, the association was significant (p=0.001, OR=19.50), but not in those with Skin Type IV (p=0.490). A significant association was also observed in individuals older than 30 years (p=0.015, OR=2.66), and in non-obese participants (p=0.003, OR=4.85). Conclusions: This study demonstrates a strong association between low serum ferritin levels and melasma, particularly in male and individuals with Fitzpatrick Skin Type III, suggesting that iron storage depletion may play a role in melasma pathogenesis. Future studies should explore whether iron supplementation influences melasma severity or treatment outcomes.